The dual role of the immune system in the pathogenesis of traumatic brain injury - Nikolay I. Lisianyi (Ukrainian Neurosurgical Journal, 2019)
Studies of the recent 10–15 years in the field of immunology have been obtained new data on the immune system structure, the functions of cells of innate and acquired immunity, the mechanisms of development of both immunopathological, damaging, and protective, stimulating tissue repair effect of immune reactions in the body as a whole including with TBI. The review examines the mechanism of development of the immune response to neurotrauma, which includes: 1) the initial activation of cells of innate immunity, namely microglia in the brain, 2) microglia synthesis of cytokines and attraction of peripheral immune cells into the brain parenchyma, 3) development of systemic specific immune and inflammatory reactions in the body. The article shows that immune reactions develop over time after TBI and may have a dual effect, namely, beneficial brain cleansing of dead cells and stimulating neuronal repair, and an immunopathological effect on the course of injury, which can lead to early or delayed neurodegeneration after TBI. Based on this duality of the influence of immune reactions on the course of neurotrauma, the review points to the need to further study of these immune processes during TBI, and to develop methods for targeted immunomodulation, which can significantly improve the results of treatment of acute TBI and its long-term effects.